Research on failure resistance of vehicle's skeletons. (February 2023) - Sabadka, Dusan; Molnar, Vieroslav; Fedorko, Gabriel; Knezo, Dusan
Highlights: Vehicle's skeleton weight reduced by 285.2 kg (9.74%). Verification of foam impact on the strength characteristics of thin-walled profiles. Research of thin-walled profiles in vehicle's skeleton by the three-point bend test. Research of thin-walled profiles' use in the construction of a vehicle's skeleton. Abstract: The skeleton of the means of transport must comply with the strictest criteria in terms of safety and failure resistance. The failure occurs for various reasons. However, the failure caused by external forces acting on the skeleton predominates. Such a type of failure results in the deformation of the whole skeleton structure or its parts. To reduce the failure, the skeleton must meet the requirements on ​​material, construction, strength, flexibility, statics, and other engineering areas. For this reason, among other things, an adequate strength of the skeleton construction in the context of its total weight must be aligned with number of criteria. There are different approaches and solutions to meet this criterion. One of the progressive approaches is based on a use of composite materials based on thin-walled profiles filled with polyurethane, epoxy, or other foam. The paper deals with the research of such thin-walled profiles properties in their use for skeleton construction of a specific type of means of transport. The aim of the paper is the failure analysis of closed steel profiles forming the frame of the means of transport, based on the analysis of different foam densities impact on the strength characteristics and failure size. The research on failure analysis was carried out using the 3-point bend test. From the point of view of failure size, unfilled profiles were compared and analyzed with each other, and then foam-filled profiles were selected, depending on the material used and its thickness, provided that the required mechanical properties are met. The results from research of a new vehicle skeleton model resulted in an overall weight reduction of 285.2 kg, which is 9.74%, while the required failure resistance of the skeleton had been achieved. This is a significant result, the conclusions of which can be applied in the design of various vehicles so that to increase their failure resistance in the context of vehicle's weight reduction.